The Daily Us (vs. Them) from Online to Offline: Japan's Media Manipulation and Cultural Transcoding of Collective Memories - Ogasawara, Midori (Journal of Contemporary Eastern Asia, 2019)
Since returning to power in 2012, the second Abe administration has pressured Japanese mainstream media in various ways, from creating the Secrecy Act to forming close relationships with media executives and promoting anti-journalism voices on social media. This article focuses on the growth of a jingoist group called the 'Net-rightists' ('Neto-uyo' in the Japanese abbreviation) on the Internet, which has been supporting the right-wing government and amplifying its historical revisionist views of Japanese colonialism. These heavy Internet users deny Japan's war crimes against neighboring Asian countries and disseminate fake news about the past, which justifies Prime Minister Shinzo Abe's hostile diplomatic policies against South Korea and China. Over the past years, the rightist online discourses have become powerful to such an extent that the editorials of major newspapers and TV reports shifted to more nationalist tones. Who are the Neto-uyo? Why have they emerged from the online world and proliferated to the offline world? Two significant characteristics of new media are discussed to analyze their successful media manipulation: cultural transcoding and perpetual rewriting of collective memories. These characteristics have resulted in constructing and reinforcing the data loops of the 'Daily Us' versus Them, technologically raising current diplomatic tensions in East Asia.